Rifampicin Induced Acute Interstitial Nephritis And Exfoliative Dermatitis Complicating Pulmonary Tuberculosis - A Case Report (BIRDEM Medical Journal, 2017)
Rifampicin is one of the most effective antitubercular agents. Among its rare adverse effects, acute interstitial nephritis is noteworthy. Furthermore, exfoliative dermatitis caused by rifampicin is quite uncommon. Simultaneous occurrence of the both complications in the same patient has not been reported so far. Here we describe a case history of a 76-year-old male who developed rifampicin induced acute interstitial nephritis and exfoliative dermatitis at the same time.Birdem Med J 2017; 7(2): 168-171